2012
DOI: 10.1021/am301373n
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Based Hydrogels to Make Metal Nanoparticle-Containing Reduced Graphene Oxide-Based Functional Hybrid Hydrogels

Abstract: In this study, stable supramolecular hydrogels have been obtained from the assembly of graphene oxide (GO) in presence of polyamines including tris(aminoethyl)amine, spermine, and spermidine [biologically active molecule]. One of these hydrogels has been well characterized by various techniques including field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray diffraction (XRD) study, and Raman spectroscopy. TEM and AFM studies of one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
127
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 65 publications
5
127
0
Order By: Relevance
“…11 Hydrogels self-assembled by mixing GO and cationic polymers in water were later also reported by others. [13][14][15] GO-polyamine hydrogels, including tris(aminoethyl)-amine, spermine, and spermidine, were formed driven by electrostatic interaction (mechanical properties not shown). 13 GO/branched polyethylenimine (PEI) hydrogels were reported for organic dye removal and wastewater treatment (mechanical properties not shown).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Hydrogels self-assembled by mixing GO and cationic polymers in water were later also reported by others. [13][14][15] GO-polyamine hydrogels, including tris(aminoethyl)-amine, spermine, and spermidine, were formed driven by electrostatic interaction (mechanical properties not shown). 13 GO/branched polyethylenimine (PEI) hydrogels were reported for organic dye removal and wastewater treatment (mechanical properties not shown).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] GO-polyamine hydrogels, including tris(aminoethyl)-amine, spermine, and spermidine, were formed driven by electrostatic interaction (mechanical properties not shown). 13 GO/branched polyethylenimine (PEI) hydrogels were reported for organic dye removal and wastewater treatment (mechanical properties not shown). 16 We reported that GO-gelatin nanocomposite hydrogels having 98 wt.% water exhibited a storage modulus of 115 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO), a two-dimensional single-layer nanomaterial, is prepared from graphite by means of chemical oxidation and exfoliation [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. GO can be stably dispersed in aqueous solutions owing to its various oxygen functional groups, including hydroxyl (\ \OH), epoxy (\ \C\ \O\ \C), carbonyl (\ \C_O) and carboxyl (\ \COOH) [35][36][37][38][39][40][41][42]. Moreover, depending on these functional groups, GO can make strong covalent or noncovalent interactions with polar small molecules or polymers, and also function as nanofillers to mechanically reinforce hydrogels [43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of graphene sheets by gelators involving different noncovalent interactions is a convenient method for preparing supramolecular hydrogels [14][15][16]. Hydrogels are prepared using different kinds of linkers, some of which include polymers [3], organic molecules [17], metal oxides [18,19], DNA molecules [20], and metal nanoparticles [21]. PEI as a commercially available polymer is well-known with two structures including branched and linear.…”
Section: Introductionmentioning
confidence: 99%